Implementation of Project Based Learning Model for Enhancing Students’ Practical Skill and Scientific Literacy - Gamila Nuri Utami; Senam Senam (Universitas Lampung, 2021)
Abstract: Implementation of Project Based Learning Model for Enhancing Students’ Practical Skill and Scientific Literacy. Objectives: This study is aimed to determine the difference of implementation between project based learning and direct instruction model in chemistry teaching of acid and base matter to enhancing students’ practical skill and scientific literacy. Methods: The sampling technique was purposive sampling that obtained class XI MIPA 1 as an experimental class was taught using project based learning model, while XI MIPA 2 as a control class was taught using direct instruction model. The instruments of data collecting are test and non test. The test by using the form of a description was used to measure students' scientific literacy, while non test by using the observation sheet was used to measure students' practical skill. The data analysis used manova test at significance level of 5%. Findings: The results showed that the Hotelling's Trace value on the manova test had a significance of 0.000. Conclusion: there is a significant difference between implementation of project based learning and direct instruction model in chemistry teaching of acid and base matter for enhancing students’ practical skill and scientific literacy wholly and partially. Keywords: Project based learning, practical skill, scientific literacy